Evaluating the Potential of Utilizing Silica Sand for Thermal Energy Storage Applications: A Case Study of New Luika Gold Mining in Songwe Region, Tanzania. (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2025)
This research investigates the potential application of silica sand from New Luika Gold Mining, Songwe Region, Tanzania, as a thermal energy storage (TES) medium. Through detailed chemical, physical, and thermophysical analyses of three silica sand samples, the sand suitability based on purity, moisture content, porosity, thermal conductivity, and stability under TES operating conditions were evaluated. The coarse silica sand sample TAN-005 demonstrated optimal properties including high silica content (97.15%), low moisture (0.0198%), and low electrical conductivity (41.6 μS/cm), making it the most promising candidate for high-temperature TES applications. The findings was found to support the viability of indigenous silica sand as a cost-effective, environmentally friendly TES medium. The significance of the findings aligns with Tanzania’s renewable energy goals.